Hydrogen Bond-Assisted Ultra-Stable and Fast Aqueous NH4+ Storage - Zhang, Xikun; Xia, Maoting; Yu, Haoxiang; Zhang, Junwei; Yang, Zhengwei; Zhang, Liyuan; Shu, Jie (Nano-micro letters, 2021)
Highlights Zero capacity fading after over 3000 cycles at 1 C. Only 6.4% capacity is lost when rate is increased by 50 times. Diffusion mechanism of formation and fracture of hydrogen bonds is proposed. Aqueous ammonium ion batteries are regarded as eco-friendly and sustainable energy storage systems. And applicable host for NH 4 + in aqueous solution is always in the process of development. On the basis of density functional theory calculations, the excellent performance of NH 4 + insertion in Prussian blue analogues (PBAs) is proposed, especially for copper hexacyanoferrate (CuHCF). In this work, we prove the outstanding cycling and rate performance of CuHCF via electrochemical analyses, delivering no capacity fading during ultra-long cycles of 3000 times and high capacity retention of 93.6% at 50 C. One of main contributions to superior performance from highly reversible redox reaction and structural change is verified during the ammoniation/de-ammoniation progresses. More importantly, we propose the NH 4 + diffusion mechanism in CuHCF based on continuous formation and fracture of hydrogen bonds from a joint theoretical and experimental study, which is another essential reason for rapid charge transfer and superior NH 4 + storage. Lastly, a full cell by coupling CuHCF cathode and polyaniline anode is constructed to explore the practical application of CuHCF. In brief, the outstanding aqueous NH 4 + storage in cubic PBAs creates a blueprint for fast and sustainable energy storage.